Reproductive biology of skipjack tuna Katsuwonus pelamis in Majene Waters, West Sulawesi Province, Indonesia - MUHAMMAD NUR; TENRIWARE TENRIWARE; SRI UTAMI; ADIARA FIRDHITA ALAM NASYRAH; RASTI SAPRI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nur M, Tenriware, Utami S, Nasyrah AFA, Sapri R. 2024. Reproductive biology of skipjack tuna Katsuwonus pelamis in Majene Waters, West Sulawesi Province, Indonesia. Biodiversitas 25: 2828-2835. Skipjack tuna Katsuwonus pelamis (Linnaeus, 1758) is a major global fishery resource and a target species in West Sulawesi Province. Therefore, this research aimed to examine various biological factors related to skipjack tuna, including sex ratio, Gonad Maturity Stage (GMS), Gonadosomatic Index (GSI), size at first maturity, and fecundity. The primary objective was to provide essential data that supported the sustainable management of skipjack tuna in Majene Waters located in West Sulawesi, Indonesia. Fish samples were collected by fishermen using purse seine fishing gear and hand lines, and landed at Fish Landing Sites Majene. This research was carried out from July 2023 to February 2024, with analysis performed at the Fisheries Department Laboratory, Universitas Sulawesi Barat. The analysis stages included measuring fish total body length with an accuracy of 0.1 mm and weighing the body weight using a digital scale with an accuracy of 0.01 g. A total of 340 skipjack tuna were sampled, consisting of 192 males and 148 females, indicating a nearly balanced sex ratio. The spawning season appeared to extend throughout the year, with a peak spawning period from November to February. This analysis result found five levels of gonad maturity, including GMS I (immature), GMS II (maturing), GMS III (mature), and GMS IV (ripe and running), as well as GMS V (spent). The size at first maturity for males skipjack tuna was 400.2 mm, ranging from 386.6-402.3 mm. Meanwhile, the size at first maturity for females varied between 396.6 and 462.3 mm, averaging 420.2 mm. The reproductive potential of skipjack tuna was relatively high, with an average fecundity ranging from 203,377-739,820 eggs.